A Question of Leadership - Leslie, Keith (Ascent Audio, 2021)
Whether planned or unexpected, change presents leaders with their toughest sustained challenges-regardless of the leader's seniority or the organization's size. For many leaders, change brings drama-and the replaying of familiar stories. In A Question of Leadership, Keith Leslie provides a wide range of illustrative case studies derived from both research and his firsthand experience in the public and private sectors as a former partner at both Deloitte and McKinsey. Each chapter first provides an engaging narrative that presents a relatable leadership dilemma, before an analysis of what works and when, followed by a selection of research which supports this thesis and, finally, actionable advice for leaders who find themselves in comparable circumstances. Alongside their individual takeaways, each of these case studies are united behind an overarching thesis: the failure of many change initiatives is caused by the leader's inability to fully consider the consequences and magnitude of the situation. Whether they consider it "just a game," or they are "gaming the system," they often fail to recognize the full consequences of the change initiative. Across business and society, the prevalence and impacts of such short-sighted mistakes have become more overt than ever following the onset of the ongoing COVID-19 pandemic.